RESPONSE OF GROWTH, RESULTS AND QUALITY OF BROKOLY VARIETIES (Brassica oleracea L. var. Italica) IN VARIOUS SPACING PLANTS - Dwi Aprilia Ningrum; Lagiman Lagiman; Oktavia Sarhesti Padmini (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2018)
Broccolli (Brassica oleracea L. Var. Italica) is one of the vegetables variety which has lots of nutrients, and it also has high economic value. This research aimed to find out the response of growth, yield, and quality of broccolli (Brassica oleracea L. Var. Italica) varieties among the plant spacings. This research was conducted in Mei until August 2017 in Weron Hamlet, Umbulharjo Village, Cangkringan Subdistrict, Sleman Residence in DIY Province. This research used randomized complete block design (RCBD) which was arranged factorially. It consisted of two factors with three replications. The first factor is broccolli variety that are Griifn (V1), Green Super (V2), and Chief no.2 (V3). The second factor is spacing plants which consists of 4 levels, that are 65cm x 60cm (J1), 70cm x 60cm (J2), 75cm x 60cm (J3), and 80cm x 60cm (J4). The observation data were analyzed for its diversity at the level α = 5%. In addition, Duncan Multiple Range Test (DMRT) at the level α = 5% was used to find out the difference on averange treatment. The result showed that there is an interraction between the treatment variety of broccolli and the plant spacings in harvest parameters. The variety of Green Super which is 80 cm x 60 cm has a good result to broccolli yield. This yield is compared to other treatments. However, the yield is still low if it is seen from the description of variety.Keywords: broccoli, varieties, Plant spacing